Stress Distributions in the Cattaneo–Mindlin Problem on a Contact With Slip and Adhesion of Two Cylindrical Bodies - Klimchuk, Taras; Ostryk, Volodymyr (Frontiers in Mechanical Engineering, 2020)
Two-dimensional Cattaneo – Mindlin problem on a partial slip contact between two elastic bodies of the same material is considered in classical statement for circular cylinders as well as in more general statements: for non-circular cylinders with higher order of touch and cylindrical bodies with a wavy periodic surface. Stress distributions are found both in the contact area and inside the bodies. The question of how the friction affects a formation of stick zone in the contact area and distribution of maximum tangential stress within the bodies is investigated.